Retinopathy in non diabetics, diabetic retinopathy and oxidative stress: a new phenotype in Central Africa? - Longo-Mbenza, Benjamin (International Journal of Ophthalmology Press, 2014)
AIM: To evaluate the rates of retinopathy without diabetes and diabetic retinopathy (DR), associated with some markers of oxidative stress, antioxidants and cardiometabolic risk factors. METHODS: We determined the prevalence of DR in 150 type 2 diabetes mellitus (T2DM) patients, that of retinopathy in 50 non diabetics, the levels of body mass index (BMI), waist circumference (WC), blood pressure, lipids, 8-isoprostane, 8-hydroxydeoxyguanosine (8-OHdG), gamma-glutamyl transferase GT (GGT), oxidized low-density lipoprotein (OxLDL), thiobarbituric acid reacting substances (TBARS), reduced glutathione (GSH), superoxide dismutase (SOD), uric acid, creatinine, albumin, total antioxidant status (TAOS), zinc, selenium, magnesium, vitamin C, vitamin D, vitamin E, glucose, apolipoprotein B (ApoB). RESULTS: The prevalences of DR at 53y and Rtp at 62y were 44% (n=66) and 10% (n=5), respectively. The highest levels of 8-isoprostane, 8-OHdG, TBARS, SOD, and OxLDL were in DR. The lowest levels of vitamin D, vitamin C, TAOS, and vitamin E were in DR. In the case-control study discriminant analysis, the levels of vitamin C, vitamin D, ApoB, 8-OHdG, creatinine, Zn, vitamin E, and WC distinguished significantly non-diabetics without DR (controls), T2DM patients without DR and T2DM patients with DR. CONCLUSION: Anticipation of DR onset is significantly associated with the exageration of oxidative stress biomarkers or decrease of antioxidants in African type 2 diabetics. Prevention of oxidative stress and abdominal obesity is needed. Supplementation in vitamin C, D, and E should be recommended as complement therapies of T2DM.